Historical Approach and Philological Approach as Methodological Reasoning in the Study of the al-Quran (A Conceptual Study): Historical Approach dan Philological Approach sebagai Nalar Metodologis dalam Kajian Studi al-Quran (Sebuah Telaah Konseptual) - Rohman, Moh. Mujibur; Wasik, Wasik; Hidayat, Muhammad Syaiful Bahri; Yaqin, Moh. Ainul; Fadoli, Ach.; Azhari, Mohammad Nadzir (Al-Maktabah: Jurnal Studi Islam Interdisiplin, 2024)
As a source of Islamic law, the study of the al-Quran is an interesting study. Reactualization of understanding of the content of the al-Quran needs to be done so that the al-Quran remains pious li kulli zaman wa makan. The al-Quran as a revelation and source of law handed down from the Almighty (Allah azza wa jalla) cannot possibly be understood from a scientific aspect. Two approaches, namely the historical approach and the philological approach. It is important in understanding "the texts" or the Quran as a guide (hudan li al-muttaqin) so that many maziyah are revealed in it. This article is conceptual research with a descriptive qualitative type. Data collection is carried out by means of documentation or library research. The author attempts to conduct a review of the study of the al-Quran with a focus on historical approaches and philological approaches. Both are part of the study of Islamic studies. Data collected from several literature or sources is then analyzed by displaying, reducing and drawing conclusions. The research results show that the historical approach is closely related to the study of the Quran, especially since the text of the al-Quran was revealed gradually in accordance with the legal conditions of society at that time, shalih kulli zaman wa makan. A historical approach is very necessary to understand the meaning of a verse, sabab al-nuzul. Philological approach is an important thing in studying the al-Quran which has been passed down for centuries (14 centuries). Its application in the study of the al-Quran is such as knowing interpretation methods, be it tahlīlī, ijmalī, muqaran and mawdzu'ī (thematic).